Three recent ice entrapments of Arctic cetaceans in West Greenland and the eastern Canadian High Arctic - Heide-Jørgensen, MP; Richard, P; Ramsay, M; Akeeagok, S (NAMMCO Scientific Publications, 2002)
Three ice entrapments of Monodontids have been reported in the western North Atlantic since 1993. Hunters in Disko Bay, West Greenland, discovered one in March 1994 that included about 150 narwhals (Monodon monoceros). The entrapment occurred during a sudden cold period which caused ice to form rapidly. The trapped whales were subject to hunting, but about 50 of the killed whales could not be retrieved in the ice. The whales were trapped in a small opening in the ice and because of that they would probably have succumbed even if not discovered by hunters. Two entrapments involving white whales or belugas (Delphinapterus leucas) occurred in the eastern Canadian Arctic in May 1999; one in Lancaster Sound discovered by polar bear (Ursus maritimus) researchers and one in Jones Sound discovered by hunters. The first included one bowhead whale (Balaena mysticetus) and about 40 belugas that were being preyed upon by polar bears. The second involved at least 170 belugas, of which about 100 were killed by polar bears and 17 were taken by hunters. The entrapments in Disko Bay and Jones Sound both occurred in areas where entrapments have previously been reported, whereas the one in Lancaster Sound was in a new area.